Highly independent dual-band permittivity sensors for simultaneous measurement of solid materials - Alam, Syah; Zakaria, Zahriladha; Surjati, Indra; Shairi, Noor Azwan; Alaydrus, Mudrik; Firmansyah, Teguh (2023)
This study proposes the design of a dual-band independent microwave sensor for the simultaneous detection of the permittivity of various solid materials. The sensor utilizes two U-shaped resonators that are connected by a microstrip feed line with an impedance of 50 Ω. The 1st resonator operates at a frequency of 1.21 GHz and the 2nd resonator operates at 2.1 GHz. The independence of the resonators was determined using Pearson correlation analysis in a scenario where the Materials Under Test (MUT) were placed in the sensing hotspot area of both resonators. Results indicated a low correlation coefficient (r < 0.2) between the resonant frequencies of the two resonators when the MUT was placed in both resonators simultaneously, with X2 = 0.01 and Y1 = 0.076. This proposed sensor design has the potential to be a valuable solution for the simultaneous detection of different permittivity of solid materials with high accuracy in various fields such as the food industry, biomedical applications, and material quality control in the pharmaceutical industry.